THE LIFE OF HELL OWNERS IN THE QUR’AN - Qamar, Syamsul; Galib, M, Muhammad; Amin, Muhammadiyah; Firdaus, Firdaus (Jurnal Diskursus Islam, 2020)
This paper elaborates on the life of the inhabitants of hell in the Koran. This type of research is a descriptive qualitative library research. The approaches used in this research are interpretive, theological, philosophical and semantic approaches. Data were collected using the method of exegesis, namely the maudu’i method, both primary data in the form of Qur’anic expressions starting from the form of verses, clauses, phrases, to vocabulary related to problem studies, as well as secondary data in the form of data. The decline of the Koran, linguistic data, and data relating to the theory of knowledge. The collected data interpreted with textual, linguistic, systemic, and socio-historical interpretations. The results of the research show that the life of the hereafter becomes the belief of every human being that there is life after this world life, which symbolized by the life of heaven and life of hell. The life of the inhabitants of hell depicted in terms of neither living nor dying. This is because their lives filled with torments due to the bad things they do while living in this world and that torture has a bad result in the form of death.